2006
DOI: 10.4161/cbt.5.11.3297
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of mutant K-ras expression by adenovirus-mediated siRNA inhibits the in vitro and in vivo growth of lung cancer cells

Abstract: The ras mutation, which is observed in 20-30% of human nonsmall cell lung cancers (NSCLCs), is one of common genetic alterations and has been proposed to be a prognostic factor in lung cancer. Oncogene ras appears to be essential for tumor progression and maintenance. Several therapeutic agents have been developed to inhibit ras, such as FTIs and antisense oligonucleotides. A new tool for blocking oncogenes in cancer cells has emerged with the discovery that RNA interference can specifically silence expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 0 publications
2
42
0
1
Order By: Relevance
“…This mutation is a key initiator, as evidenced by its presence in PanIN lesions (Kanda et al 2012;Murphy et al 2013) and the production of PanIN lesions in oncogenic Kras-driven GEMMs (Hezel et al 2006;Perez-Mancera et al 2012a). While some PDAC cell lines in two-dimensional (2D) culture can tolerate shRNA-mediated KRAS extinction (Singh et al 2009), most PDAC cells remain highly addicted to oncogenic KRAS for tumor maintenance in three-dimensional (3D) culture (Zhang et al 2006;Fujita-Sato et al 2015) and inducible oncogenic Kras GEMMs with advanced tumors (Collins et al 2012;Ying et al 2012). These data strongly support the view that KRAS is a prime therapeutic target for PDAC.…”
Section: The Kras Oncogene Signaling Networkmentioning
confidence: 99%
“…This mutation is a key initiator, as evidenced by its presence in PanIN lesions (Kanda et al 2012;Murphy et al 2013) and the production of PanIN lesions in oncogenic Kras-driven GEMMs (Hezel et al 2006;Perez-Mancera et al 2012a). While some PDAC cell lines in two-dimensional (2D) culture can tolerate shRNA-mediated KRAS extinction (Singh et al 2009), most PDAC cells remain highly addicted to oncogenic KRAS for tumor maintenance in three-dimensional (3D) culture (Zhang et al 2006;Fujita-Sato et al 2015) and inducible oncogenic Kras GEMMs with advanced tumors (Collins et al 2012;Ying et al 2012). These data strongly support the view that KRAS is a prime therapeutic target for PDAC.…”
Section: The Kras Oncogene Signaling Networkmentioning
confidence: 99%
“…RNA interference (RNAi) [1][2][3] was first discovered in Caenorhabditis elegans as a potent gene-silencing mechanism. 4 The inhibition of specific gene expression by means of RNAi has also been achieved in mammalian cells by directly introducing short dsRNA (siRNA) into cells, which avoids a response evoked by long dsRNA.…”
Section: Introductionmentioning
confidence: 99%
“…90% of pancreatic cancers, 50% of colon cancers, 30% of lung cancers) supports the idea that aberrant Ras activation is a driving force in the development and advancement of these malignancies [10]. The use of in vitro knockdown studies [45] and transgenic mouse models [46], [47] further confirmed this idea that mutant Ras is highly transforming.…”
Section: Ras Activation In Breast Cancersupporting
confidence: 53%